2015
DOI: 10.4067/s0717-75182015000400014
|View full text |Cite
|
Sign up to set email alerts
|

Los alimentos y bebidas ultra-procesados que ingresan a Colombia por el tratado de libre comercio: ¿influirán en el peso de los colombianos?

Abstract: Los alimentos y bebidas ultra-procesados que ingresan a Colombia por el tratado de libre comercio ¿infl uirán en el peso de los colombianos? 409Jhon Bejarano-Roncancio (1) Edna Magaly Dora Hilda Aya-Baquero (3) Diana C. Parra (4,5) (1 Los alimentos y bebidas ultra-procesados que ingresan a Colombia por el tratado de libre comercio ¿infl uirán en el peso de los colombianos? Ultra-processed foods and beverages products entering Colombia through international trade agreements. Will they have an impact on the wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…In this way, the consumer is exposed to an offer of products that compete with traditional foods prepared in a homemade style, leading to a loss of family traditions. Likewise, these trade policies favor large food industries such as transnational companies, with extremely high sales that grant them certain political [20]. Therefore, policies are essential for the regulation of the baby food market in order to ensure infants' well-being.…”
Section: Us Companies Like Beech Nut and Gerber Recommend 4 Months mentioning
confidence: 99%
“…In this way, the consumer is exposed to an offer of products that compete with traditional foods prepared in a homemade style, leading to a loss of family traditions. Likewise, these trade policies favor large food industries such as transnational companies, with extremely high sales that grant them certain political [20]. Therefore, policies are essential for the regulation of the baby food market in order to ensure infants' well-being.…”
Section: Us Companies Like Beech Nut and Gerber Recommend 4 Months mentioning
confidence: 99%
“…Ultra-processed foods contributed an average of 16.0% of the total daily calories in Colombia in 2005 5 . However, the combination of market forces, the increase in confidence to invest in the country following the end of the armed conflict, and the increase in purchasing power suggest an accelerated growth in the purchase and consumption of ultra-processed foods in the country 12 . Colombia is experiencing a nutritional, economic, and demographic transition, characterized by the decrease in the consumption of traditional meals, and an increase in urbanization and income, influenced by changing structures in the labor market 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Colombia is a country with growing levels of overweight and obesity [ 1 , 2 ] and related non-communicable diseases such as cardiovascular disease, diabetes, and cancer [ 3 , 4 ]. The increase in overweight and obesity has been accompanied by a diet characterized by high levels of sugar-sweetened beverages (SSBs) and other foods high in nutrients of concern (e.g., high in added sugar, added sodium, or added saturated fat) [ 5 , 6 ]. For example, a recent study found that of the Colombian packaged food supply, approximately 66 to 80% of packaged foods and drinks exceed thresholds for nutrients of concern set by international nutritional profile models [ 7 ].…”
Section: Introductionmentioning
confidence: 99%